2010
DOI: 10.1142/s0192415x10008299
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effects of Acupuncture on Patients with Chronic Neck Myofascial Pain Syndrome: A Single-Blind Randomized Controlled Trial

Abstract: Chronic neck myofascial pain syndrome (MPS) is a common disorder seen in clinics. There is no gold standard method to treat myofascial pain. We investigated the effects of acupuncture on patients with chronic neck MPS by a single-blind randomized controlled trial. A total of 35 patients were randomly allocated to an acupuncture group (AG) or a sham acupuncture group (SG). Each subject received acupuncture treatment twice per week for three consecutive weeks. The primary outcome measure was quality of life as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Another open and prospective study found a positive effect of dry needling comparable with physical therapy in deactivation of trigger points (Rayegani et al 2014 ). Acupuncture has also been reported to be partially effective in a controlled study (Sun et al 2010 ).…”
Section: Treatmentmentioning
confidence: 96%
“…Another open and prospective study found a positive effect of dry needling comparable with physical therapy in deactivation of trigger points (Rayegani et al 2014 ). Acupuncture has also been reported to be partially effective in a controlled study (Sun et al 2010 ).…”
Section: Treatmentmentioning
confidence: 96%
“…Finally, one study 25 did not report blinding. Three studies 17 20 21 reported part of their results in graphical form, one study 11 reported its results as median (IQR), and three studies [28][29][30] did not report any detailed data with mean±SD. Therefore, these studies were deemed to be at high risk of incomplete outcome data and selective reporting.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, they did not experience any increase in pain. Sun et al 11 reported that one patient who received MA developed bruises over the acupuncture point region after the end of the third session. No other study reported any adverse events.…”
Section: Mejuto-vázquez Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments of MTrP include manual therapies [1], physical therapy modalities [25], needling therapy (including MTrP injection [26], dry needling [27][28][29], acupuncture [30][31][32], percutaneous soft tissue release [33], and subcutaneous needling [34]), or oral medicine. Eliminating any perpetuating factors and introducing adequate education and home programs to patients are also important [1,35].…”
Section: Treatment Of Myofascial Trigger Pointmentioning
confidence: 99%